Digital legal rights for suspects: users' perspectives and PACE safeguards - Kemp, Vicky (University of Nottingham, 2018)
Research has consistently shown that many people do not understand their legal rights when arrested by the police. In seeking to help address this problem, a prototype App was developed to provide information to suspects when detained by the police. The prototype was tested with 100 detainees in two large custody suites and the findings are presented in this report. A number of issues are addressed, including police decision-making and the processing of cases, access to legal advice, users’ perspectives of fairness in the criminal process, and the potential for technology to enhance procedural safeguards. The study identified a number of problems relating to suspects’ legal rights. These include, for example, difficulties for suspects in accessing legal advice; with no provision to facilitate a confidential telephone conversation between a solicitor and their client. There were also identified long delays, with the average length of detention being over 17 hours in both police stations – almost double the time identified in an earlier study. Before proceeding, it is important that the gaps identified between the law in books and the law in action are addressed so that information about suspects’ legal rights, contained in an App, reflect practice on the ground.